Injuries incidence in Brazilian swimmers of different strokes - Haupenthal, A.; Schutz, G.; Ruschel, C.; Faquin, A.; Menezes, F.; Pereira, S. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study was to identify the incidence, place and diagnosis of injuries in competitive Brazilian swimmers, according to the stroke. The sample was composed by 137 competitive elite swimmers. The Instrument used was a mixing questionnaire. Seventy (51%) of the evaluated athletes suffered some kind of injury. During competition, 19 athletes referred injury. The most affected segment was the shoulder (53%) and the tendinitis was the most frequent diagnosis (72%). According to each kind of stroke, it was verified: a) tendinitis was the most frequent injury for the butterfly (80%), crawl stroke (86%) and breaststroke (75%) swimmers. For medley, both the tendinitis and the muscle strain were the most observed injuries (43%); b) the most affected segment was the shoulder for the butterfly (50%), backstroke (63%), crawl (56%) and medley (44%) swimmers. The knee was the most affected segment for the breaststroke swimmers (62%).